Synthesis, Characterization and Cleavage of Linear Polymers Attached to Silica Nanoparticles Formed Using Thiol-acrylate Conjugate Addition Reactions - Khire, Vaibhav S. (2008)
This study investigates the formation of linear polymer grafts using thiol-acrylate conjugate addition reactions on nanoparticle surfaces. Silica nanoparticles were first modified with an amine functionality, followed by the attachment of a photocleavable acrylate. Dithiol-diacrylate films were attached to the particles through the surface acrylate groups at various stoichiometric ratios of thiol to acrylate by conducting amine-catalyzed conjugate addition polymerizations. The particles were then exposed to UV light to release the grafted polymer by photocleavage. The cleaved, grafted polymers were analyzed using infrared spectroscopy (IR) and gel permeation chromatography (GPC) and compared to polymers formed in the bulk, which remained unattached to the particles. The measured number and weight average molecular weights were similar for both polymer types within experimental error and increased from 2000 to 5000 g/mol and 4000 to 10000 g/mol, respectively, as the ratio of limiting to excess functionality increased from 0.8 to 1. Both number and weight average molecular weights followed the trend of step growth polymers with the highest molecular weight achieved for stoichiometric monomeric mixtures. Surface coverage of the nanoparticles was estimated using the molecular weight and thermogravimetric data and was found to be uniform (∼0.15chains/nm(2)) irrespective of the stoichiometry of the reacting monomers.